THEMATIC PROGRESSION IN RECOUNT TEXT WRITTEN BY THE EIGHT GRADE STUDENTS - Daimond Primo Philippus Purba; Siti Aisah Ginting; Fahri Haswani (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
This study was about the theme, rheme and thematic progression of students‟ recount text of the eight grade at SMP RK Budi Mulia Pematangsiantar. The aim of this study were (1) to investigate thematic progression pattern used (2) to find out the reason why the students used thematic progression in the way they did. This study was conducted by using descriptive qualitative method. The data in this study were clauses of students‟ recount text. The instrument of collecting data was elicitation technique and interview. The data were analyzed by using interactive model technique of Miles, Huberman and Saldana (2014). The result of this study were the following, (1) There were two patterns of thematic progression used in students‟ recount text, they were Theme Reteration/Constant Theme Pattern (TR/CTP), and Zig- zag/Linear Theme Pattern (Zig-zag/LTP). (2) The reason in use of thematic progression by students, they were: (a) the student‟s lack of knowledge about use of the thematic progression (b) they also less interested in writing, (c) the students got resources from reading material and (d) the students got resources from english teacher‟s explanation.